2020
DOI: 10.31258/jes.4.2.p.318-333
|View full text |Cite
|
Sign up to set email alerts
|

Motivation to Learning Mathematics and Gender as Correlates of Senior Secondary School Students’ Performance in Mathematics

Abstract: This study investigated senior secondary school students’ motivation to learning mathematics and gender as correlates of performance in mathematics. The sample consisted of 315 students from two government senior secondary schools in Lagos State, Nigeria using the quantitative research method within the blueprint of the descriptive survey research design. Data collected were analysed using percentages, means, standard deviation, independent samples t-test, Pearson Product Moment Correlation Coefficient (PPMCC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…This development may be attributed to the rewarding teaching style employed by the teacher in the classroom, which motivates students to strive for good grades in their subjects. However, these results contradict the findings of Awofala et al (2020), who claimed that extrinsic motivation does not significantly contribute to predicting students' academic performance in mathematics.…”
Section: Discussion Of Findingscontrasting
confidence: 99%
See 1 more Smart Citation
“…This development may be attributed to the rewarding teaching style employed by the teacher in the classroom, which motivates students to strive for good grades in their subjects. However, these results contradict the findings of Awofala et al (2020), who claimed that extrinsic motivation does not significantly contribute to predicting students' academic performance in mathematics.…”
Section: Discussion Of Findingscontrasting
confidence: 99%
“…This result is consistent with the findings of Abah et al (2022), who concluded that there is sufficient statistical evidence to suggest a noteworthy correlation between academic achievement in junior secondary school students' mathematics in Benue State, Nigeria's Ohimini Local Government Area and their intrinsic desire to master the subject. These findings also align with the conclusions of Awofala et al (2020), who found that intrinsic motivation is a strong predictor of senior secondary school students' performance in mathematics.…”
Section: Discussion Of Findingssupporting
confidence: 90%
“…It is evident, compared to girls, boys are more likely to choose careers related to mathematics (Watt, 2007), feel more confident and suffer less from mathematics anxiety (Ai, 2002;Hannula, 2002;Awofala & Odogwu, 2017;Awofala & Akinoso, 2017) and have higher self-concept in mathematics (Kyriacou & Goulding, 2006). Also, boys do not suffer from gender stereotyping where mathematics is viewed as a male domain (Awofala, 2008a(Awofala, , 2008bMohamed & Waheed, 2011;Awofala & Lawani, 2020;Awofala, 2017b), and have more male mathematical role models as examples to follow (Lee & Anderson, 2014). In Africa, conflicting reports on gender differences in attitudes toward International Journal on Teaching and Learning Mathematics 2020, Vol.…”
Section: Resultsmentioning
confidence: 99%
“…Students who are diligent make resolutions to be successful in mathematics classrooms as they try to comprehend difficult mathematics questions by using several approaches to arriving at solutions to them. Students who display this behavior will possess the motivation to learn mathematics (Awofala & Falolu, 2017;Awofala, Lawani & Adeyemi, 2020). Teachers can be of help in increasing students' motivation by using pedagogical strategies that rely on technology (Bester & Brand, 2013).…”
Section: Discussionmentioning
confidence: 99%